THE TYPE AND MEANING OF BAJO LANGUAGE REDUPLICATION - T. Takwa (Universitas Sembilanbelas November Kolaka, 2017)
This study is a qualitative research. This study aimed to describe in general form and meaning in reduplication of Bajo language such as (1) describing reduplication semantic features and grammatical features with dwilingga form and affixed and (2) describing the function of reduplication form of the functions of nouns, verbs, adjectives, and function numeric. Data in this study was the speech of the informant containing Bajo language reduplication system. The source of the data in this study was Bajo language spoken by the language user societies who live in the Tambea village, Hakatutobu Pomalaa District, Latambaga village, Wolo sub district where all were in the Southeast Sulawesi Province.